Opportunities For Establishing Islamic Bank in The City of Balikpapan: Business Feasibility Study Approach - Muhammad Arif Kurniawan; Beni Setyawan; Eko Priyojadmiko (Department of Islamic Banking, 2025)
Purpose – This study aims to analyze the feasibility of establishing an Islamic bank in Balikpapan through a business feasibility study approach, considering market, technical, financial, legal, as well as social and economic aspects. Methodology – The research utilizes a combination of literature reviews and surveys targeting potential customers and Islamic finance industry players to assess the feasibility of Islamic banking in Balikpapan. Findings – The study reveals that high public interest in Islamic banking services, along with supportive government policies and regional economic growth, significantly enhances the feasibility of establishing an Islamic bank in Balikpapan. However, challenges such as improving Islamic financial literacy and competition with conventional banks need to be addressed. Implications – The findings highlight the need for effective strategies to optimize market opportunities and strengthen the competitiveness of Islamic banks in Balikpapan. Financial institutions and policymakers should focus on financial literacy programs and innovative banking solutions to increase public adoption of Islamic banking. Originality – This study offers a comprehensive business feasibility analysis of Islamic banking in Balikpapan, a strategic economic hub in East Kalimantan and the gateway to the Nusantara Capital City (IKN). The research contributes to the growing discourse on expanding Islamic finance in emerging economic regions, particularly in the context of Balikpapan’s role as a vital link to IKN.